Pengaruh Penggunaan Alat Peraga pada Materi Bangun Datar Terhadap Hasil Belajar Siswa di Kelas IV - Novita, Tiara; Destiniar, Destiniar; Sunedi, Sunedi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2023)
This study aims to determine the effect of the use of teaching aids on the flat shape material on student learning outcomes in grade IV SD Negeri 31 Palembang. The research method used is an experimental method with a One-Group Pretest-Posttest Design. The data collection technique in this study was a test question in the form of a description of 5 questions. The results of this study indicate that the pretest (initial test) of students' knowledge has an average value of 58.18 with a less category after being giventreatment using a nailed board prop with the help of the demonstration method. The results of the final test (posttest) showed an average value of 74.32 in the good category and experienced an increase. Obtained t.count 9.632 and t.table 1.720 with a significant level = 0.05, (t.count 9.632 > t.table 1.720) following the criteria for testing the hypothesis if t.count > t.table then H0 is rejected and Ha is accepted. Thus there is an effect of the use of teaching aids on the flat material on student learning outcomes in class IV.